“He is just Ken:” deconstructing hegemonic masculinity in Barbie (2023 Movie) - Yakalı, Dikmen (Frontiers in Sociology, 2024)
Scholars have consistently explored Barbie in various contexts, often subjecting it to critical analysis. However, the release of the Barbie 2023 Movie has shifted our focus from Barbie to Ken, marking the first occasion when Barbie has provided a platform for exploring representations of masculinity both in the patriarchal society and in popular culture. This article aims to investigate how the 2023 Barbie movie deconstructs symbols of hegemonic and toxic masculinity and its performative aspects within the framework of (post)feminist discourse. It examines how the movie satirically employs symbols of traditional, hegemonic masculinity to challenge normative masculine ideals prevalent in our patriarchal society. The movie -through its popularity- significantly contributes to mainstream postfeminist media culture, creating a platform where discussions on masculinity, its associated crises, and the broader gender wars, along with their existential ramifications, become unavoidable. Exploring the ways masculinities are problematized and contested within postfeminist media culture, I argue that Ken, within this narrative, is positioned as the latest icon of postfeminist masculinity, symbolizing a critical juncture in the ongoing discourse on gender roles and identities.